Overwhelming pneumococcal bacteraemia in systemic lupus erythematosus. - Petros, D (1989)
An 18 year old woman presented with fulminant pneumococcal bacteraemia and subsequently died with multisystem organ failure. A search for diseases predisposing to overwhelming encapsulated bacterial infections was negative except for previously undiagnosed systemic lupus erythematosus (SLE). This case emphasises the severity of immune system dysfunction in some patients with SLE, regardless of immunosuppressive treatment. The possible relation between Fc receptor dysfunction and pneumococcal bacteraemia in SLE is discussed.